2017
DOI: 10.5114/fmpcr.2017.69272
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of fish and seafood by pregnant Polish women and the supply of docosahexaenoic acid and eicosapentaenoic acid from these products

Abstract: Background. fish and seafood are the main source of docosahexaenoic acid (dHa) and eicosapentaenoic acid (epa) in the diet. there is no available data concerning the intake of fish and seafood by pregnant polish women. Objectives. the purpose of the study was to analyze the consumption of fish and seafood by pregnant women and to estimate the daily supply of dHa and epa provided by these products. Material and methods. a fish and seafood intake questionnaire was given to 204 full-term pregnant women. Results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
2
7
1
Order By: Relevance
“…In our study, we found that 21% of the study population did not eat fish at all, which is similar to the findings of Broś-Konopielko et al (23%) [3]. Smaller percentage of women who do not eat fish has been published in the 'Health behaviors of pregnant women' report (13.4%) [33], and the study by Ługowska et al (5%) [26].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In our study, we found that 21% of the study population did not eat fish at all, which is similar to the findings of Broś-Konopielko et al (23%) [3]. Smaller percentage of women who do not eat fish has been published in the 'Health behaviors of pregnant women' report (13.4%) [33], and the study by Ługowska et al (5%) [26].…”
Section: Discussionsupporting
confidence: 90%
“…Smaller percentage of women who do not eat fish has been published in the 'Health behaviors of pregnant women' report (13.4%) [33], and the study by Ługowska et al (5%) [26]. Only 10% of our study population complied with the recommendations regarding fish consumption, which constitutes the mean from other studies in Poland, where such consumption was reported in 2.6%-19% of the women [3,14,26]. On a positive note, most respondents demonstrated a marked preference for fatty fish, which contain on average 4-fold more DHA as compared to lean fish.…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations